2004
DOI: 10.1677/jme.1.01493
|View full text |Cite
|
Sign up to set email alerts
|

The effects of FSH and of testosterone on the completion of meiosis and the very early steps of spermiogenesis of the rat: an in vitro study

Abstract: The role of FSH and of testosterone in spermatogenesis has been a matter of controversy. In the present study, we addressed the involvement of these hormones in the regulation of the completion of meiosis of male rats under in vitro conditions. In the first series of experiments, middle/late pachytene spermatocytes were cocultured with Sertoli cells for 2 weeks in the absence or presence of FSH and/or testosterone. Treatment with both FSH and testosterone reduced slightly the percentage of apoptotic germinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 51 publications
11
59
0
2
Order By: Relevance
“…Our findings also showed that FSH and testosterone have positive and somewhat overlapping effects on the meiotic divisions and the post-meiotic expression of a germ cell-specific gene (transition protein1; TP1), effects which cannot be related solely to their ability to reduce germinal cell apoptosis [24].These results have been recently confirmed by others using KO mouse models [8,9,25].…”
Section: Physiological Studies In Ex-vivo Modelssupporting
confidence: 81%
“…Our findings also showed that FSH and testosterone have positive and somewhat overlapping effects on the meiotic divisions and the post-meiotic expression of a germ cell-specific gene (transition protein1; TP1), effects which cannot be related solely to their ability to reduce germinal cell apoptosis [24].These results have been recently confirmed by others using KO mouse models [8,9,25].…”
Section: Physiological Studies In Ex-vivo Modelssupporting
confidence: 81%
“…Since this deletion of IGF-IR occurred very early during fetal life, it might be hypothesized that early loss of IGF-I signaling was compensated by other signals present in the developing testis. Hence, in order to clarify the potential implication of auto/paracrine IGF-I in Sertoli-germ cell interaction, co-culture of germ cells (Weiss et al 1997, Vigier et al 2004) together with wild-type or IGF-IR deleted Sertoli cells should be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Germinal cells were extracted from the testis by mechanical dissociation and a combination of trypsin and DNase according to Vigier et al (2004), then they were separated by centrifugal elutriation (Bucci et al 1986). The enriched spermatogonia-preleptotene spermatocytes fraction was further subjected to differential plating (12 h at 33 8C in Ham's F-12/Dulbecco's modified Eagle's medium (DMEM) (PAN-Biotech, Brumath, France) containing 0 .…”
Section: Purification and Incubation Of Germ Cellsmentioning
confidence: 99%